2018
DOI: 10.1093/tbm/ibx067
|View full text |Cite
|
Sign up to set email alerts
|

A scoping study of frameworks for adapting public health evidence-based interventions

Abstract: Evidence-based public health translation of research to practice is essential to improve the public's health. Dissemination and implementation researchers have explored what happens once practitioners adopt evidence-based interventions (EBIs) and have developed models and frameworks to describe the adaptation process. This scoping study identified and summarized adaptation frameworks in published reports and grey literature. We followed the recommended steps of a scoping study: (a) identifying the research que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
198
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(215 citation statements)
references
References 47 publications
4
198
0
1
Order By: Relevance
“…To that end, a fast‐developing body of research has aimed to provide guidance for adapting EBPs (Bernal & Domenech Rodríguez, ; Bumbarger & Kerns, ; Ferrer‐Wreder, Sundell, & Mansoory, ). A recent review suggested important similarities and differences across proposed frameworks for such adaptations (Escoffery et al, ). In deciding what components of an EBP require adaptation, some frameworks emphasized understanding and preserving core elements (e.g., Rolleri et al, ), whereas others prioritized improving the fit between the intervention and target population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, a fast‐developing body of research has aimed to provide guidance for adapting EBPs (Bernal & Domenech Rodríguez, ; Bumbarger & Kerns, ; Ferrer‐Wreder, Sundell, & Mansoory, ). A recent review suggested important similarities and differences across proposed frameworks for such adaptations (Escoffery et al, ). In deciding what components of an EBP require adaptation, some frameworks emphasized understanding and preserving core elements (e.g., Rolleri et al, ), whereas others prioritized improving the fit between the intervention and target population.…”
Section: Introductionmentioning
confidence: 99%
“…In deciding what components of an EBP require adaptation, some frameworks emphasized understanding and preserving core elements (e.g., Rolleri et al, ), whereas others prioritized improving the fit between the intervention and target population. In consolidating their review results, Escoffery et al () concluded that existing adaptation frameworks contained some combination of up to 11 distinct steps, including (but not limited to) selection of the EBP in question; consultation with experts and/or stakeholders; pilot testing of the modified EBP; and eventual full‐scale implementation and testing.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this manuscript was to describe the adaptation process of Project UPLIFT for Black and Hispanic PWE. The Adaptation framework outlined by Escoffery and colleagues [53] was generally followed and based on input from experts and stakeholders, each site implemented modifications. The MSM team found that no changes were necessary for the Project UPLIFT curriculum itself, however, recruitment language needed to be slightly modified for Black PWE.…”
Section: Resultsmentioning
confidence: 99%
“…In this adaptation process, both MSM and NYU learned that it was important to explore the need to adapt the program's curriculum but also to examine how best to deliver the proposed EBI in the new community. The review by Escoffery and colleagues [53] suggested common steps undertaken in the adaptation process for EBIs. In the current paper, the MSM and NYU teams described the processes from the point of intervention selection (step #3) through implementation and evaluation of the adapted EBIs (step #11).…”
Section: Lessons Learnedmentioning
confidence: 99%
“…This study aimed to: i) explore researchers' and practitioners' views on adaptation guidance as summarized in two recent scoping reviews by Escoffrey et al (2018) and Wang et al, (2018) [9,10], ii) identify potential improvements to increase the practicality of adaptation frameworks in real world settings and iii) identify future opportunities to advance the adaptation literature to achieve better public health outcomes.…”
Section: Aimsmentioning
confidence: 99%